Aboriginal patients driving kidney and healthcare improvements: recommendations from South Australian community consultations. (7th July 2022) - Kelly, Janet; Stevenson, Tahlee; Arnold‐Chamney, Melissa; Bateman, Samantha; Jesudason, Shilpanjali; McDonald, Stephen; O'Donnell, Kim; Pearson, Odette; Sinclair, Nari; Williamson, Inawinytji
Abstract: Objective : To describe the experiences, perceptions and suggested improvements in healthcare identified by Aboriginal patients, families and community members living with kidney disease in South Australia. Methods : Community consultations were held in an urban, rural and remote location in 2019 by the Aboriginal Kidney Care Together – Improving Outcomes Now (AKction) project and Kidney Health Australia. Consultations were co‐designed with community members, using participatory action research, Yarning, Dadirri and Ganma Indigenous Methodologies. Key themes were synthesised, verified by community members and shared through formal and community reports and media. Results : Aboriginal participants identified the importance of: family and community and maintaining their wellbeing, strength and resilience; the need for prevention and early detection that is localised, engages whole families and prevents diagnosis shock; better access to quality care that ensures Aboriginal people can make informed choices and decisions about their options for dialysis and transplantation, and; more Aboriginal health professionals and peer navigators, and increased responsiveness and provision of cultural safety care by all kidney health professionals. Conclusion : Aboriginal community members have strong and clear recommendations for improving the quality and responsiveness of health care generally, and kidney care specifically. Implications for public health : Aboriginal people with lived experience of chronic conditions wish to significantly inform the way care is organised and delivered.